Squeeze casting of Zn-Bi monotectic alloy - Erturan, Hakan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1994., 1994)
Zn- 1.9 wt.% Bi monotectic alloy was squeeze cast under pressures of 50, 85 and 120 MPa at a constant die temperature of 250 °C. The same die was used also for the gravity cast specimens of the same alloy. For comparison purposes the pure zinc castings were gravity cast and squeeze cast under 120 MPa at a die temperature of 400 °C. It was found that the porosity level in the castings were decreased with the application of squeezing pressure which resulted in an increase in tensile strength and hadness values. However, the microstructural examination showed that the segregation tendency of bismuth phase along the centerline was increased with increasing pressure and caused an inhomogeneous distribution of bismuth phase in the radial direction. The distribution of bismuth phase was also inhomogenous in the longitudinal direction due to gravitational segregation. In the macrostructural examination of the samples, the average grain size was found to decrease as the squeezing pressure was increased. A variation in grain size along longitudinal axis of the specimens was also observed. The grains were coarser near the bottom end and were finer near the punch end of castings. It appears that the lower part of the castings were solidified before pressure application.
Keywords: Solidification.